Combination therapy for rheumatoid arthritis with rituximab and leflunomide(preliminary results of the Russian ARBITR Registry) - Evgeniy L'vovich Nasonov (Научно-практическая ревматология, 2011)
The paper analyzes the efficiency and tolerability of a combination of rituximab (RTM) and leflunomide (LEF) for the treatment of rheumatoid arthritis (RA) versus the conventional combination of RTM and methotrexate (MT). The results of 24-week therapy were assessed in the RA patients included into the Russian Biological Therapy Register. A good effect of therapy was achieved in 31.8% of the patients who had received RTM+LEF (p = 0.1). The development of clinical remissions in RA was observed at a practically equal frequency of 13.6 and 11.7%, respectively. The doses of glucocorticoids and nonsteroidal anti-inflammatory drugs used in concurrent anti-inflammatory therapy could be substantially reduced in both groups. In both groups, the rate of side effects was very equal: 21.7% for the RTM+LEF group and 25.7% for the RTM+MT group. Thus, the combination therapy of RTM and LEF in real clinical practice is not considerably different from the most commonly used combination of RMT and MT in efficiency and tolerability and may be successfully used if there are any contraindications to the use of MT.